Prevalencia, factores asociados y complicaciones de ruptura prematura de membranas en pacientes ingresadas al Hospital Isidro Ayora de Loja. - Viteri Ortega, Karen Andrea (2016)
Premature rupture of membranes (PRM) is a condition obstetrics and constitutes a public health problem increasing the risk of morbi- mortality maternal and perinatal complications, which determines short and long term. This study aims to determine the prevalence, risk factors and more frequent maternal and fetal complications RPM higher frequency that presented patients admitted to the service of Obstetrics Gynecological Hospital Isidro Ayora from Loja City during the period June 2015-2016. A retrospective, descriptive study was conducted with a universe of 5093 pregnant women, taking as example 53 patients who meet the inclusion criteria. According to the results, the prevalence corresponds to 1.04% RPM patients, appearing most often aged between 15- 20 years with 67.92%; Likewise predominant in women first gestants with 67.92% in those with a gestational age ranging between 32- 36.6 weeks with 62.26; more predominant in rural areas with 52.83%, in patients patients with a history of urinary tract infection 66.03%, maternal complications such as chorioamnionitis with 9.43% and fetal complications such as premature birth with 77.35%; and respiratory distress syndrome with 38.30%. These findings show the main risk factors for RPM and the absence of preventive measures, which can serve as clinical markers that, can detect the disease in early clinical stages and prevent progression to severe forms. Key words: Premature rupture of membranes (PRM), Complications